2018
DOI: 10.1002/ajhb.23143
|View full text |Cite
|
Sign up to set email alerts
|

Differences in relationships of maternal and paternal age at childbirth with body fat distribution in offspring

Abstract: Objectives: Although delayed parenthood has been linked to various adverse health outcomes in offspring, little attention has been given to the relationship between an increased parental age at childbirth and fat distribution in offspring. We aimed to determine the relationship between parental age at childbirth and body fat partitioning in Chinese children. Methods: A total of 463 children (mean age, 8 years; 43% female) were recruited. Dual-energy X-ray absorptiometry was used to determine the fat mass (FM) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…However, a recent study from China has shown that maternal age younger than 28 years could predict pediatric overweight or obesity (60). Other studies also supported that although children of mothers with an advanced maternal age exhibited a higher BMI, mother's age at pregnancy has not been identified as a predictor of overweight for children (61,62). Based on all known evidence, we infer that the association between advanced maternal age and the early occurrence of AR was mediated by immediate neonatal outcomes such as intrauterine growth restriction or preterm birth.…”
Section: Discussionmentioning
confidence: 99%
“…However, a recent study from China has shown that maternal age younger than 28 years could predict pediatric overweight or obesity (60). Other studies also supported that although children of mothers with an advanced maternal age exhibited a higher BMI, mother's age at pregnancy has not been identified as a predictor of overweight for children (61,62). Based on all known evidence, we infer that the association between advanced maternal age and the early occurrence of AR was mediated by immediate neonatal outcomes such as intrauterine growth restriction or preterm birth.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to individual's own factors,parentalfactors have been suggested to affect the development of overweight and obesity in the offspring.For example,high maternal age at childbirth has been associated with increased body fat accumulation in the offspringduring chilhdood 35 and increased BMIduring adolescence 36 .Noticeably, own smoking may be a marker of the accumulation of unhealthy lifestyle factors and thus increase the risk of overweight 31 . However,active smoking may also reduce the weight of an individual.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Recent data indicated that children of fathers aged >35 years at childbirth had lower BMI than children of fathers aged 31–35 and ≤30 years ( 51 ). In China, a higher paternal age may have negative effects on children's health; that is, higher income families can afford more high-energy foods and access more sedentary modes of transportation and leisure ( 52 ). In summary, the impact of paternal and maternal age at childbirth on nutritional statuses is currently unclear.…”
Section: Discussionmentioning
confidence: 99%